Propostas para o ensino de física com o uso da plataforma arduino - CUNHA, Douglas Barros da (2023)
This paper discusses the current context of physics teaching, and some challenges faced by teachers, especially those of basic education, but not restricted to them, taking into account technological advances and their use in the classroom. The following is the Arduino hardware platform, its main features, as well as the features offered by it and the advantages of using it for the study and verification of physical concepts. We then discussed the central role of experimentation in the process of teaching science learning, more specifically in physics, and how Arduino can be useful in this process of data acquisition and in the development of toy models. Following are some articles from the field of research in Physics Teaching that address proposals for the use of Arduino as a didactic resource to boost the classroom environment. Finally, as an example of a low cost experiment, we present a circuit with Arduino board and LDR (Light Dependent Resistor) light sensor.